Design And Creation Of A Pension Fund Management Information System At PT. Kaltim Group Fertilizer Pension Fund Web-based - Nanda, El; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2024)
PT. Pupuk Kaltim Group Pension Fund is the largest fertilizer producer in Asia, facing challenges in managing pension funds for thousands of employees with various retirement ages. Despite using the Accounting Information System (AIS), there are still problems such as manual confirmation through WhatsApp messages and administration of retired employees who still use paper, potentially causing data errors. To handle these problems, a web-based pension fund management was designed and built using Unified Modeling Language (UML) system modeling, PHP as a programming language and MySQL as a database. With this application, it is expected to increase the efficiency of employee pension fund management.